Value Creation and Value Appropriation in Innovative Coopetition Projects - Paul Chiambaretto; Jonathan Maurice; Marc Willinger (M@n@gement, 2020)
This article provides a formal model of the value creation-appropriation dilemma in coopetition for innovation, that is, alliances among competing firms. The model determines the levels of cooperation that maximize the profit of each firm in an innovative coopetition agreement regardless of the number of firms and their respective budget endowments dedicated to the coopetitive project. We answer the following questions: within an innovative coopetition agreement, will the partners cooperate more or less when their budget endowments change? What is the impact on profit? When is it profitable to accept a new partner into the agreement? What happens to the remaining firms when a partner withdraws from the agreement? We show that when the coopetitive budget of the focal firm increases, the focal firm allocates a larger part of this budget to value creation activities and increases its profit. In contrast, when a partnering firm increases its coopetitive budget, the focal firm reduces its budget for value creation activities to maintain a sufficient budget for value appropriation activities. We also show that the addition of a competitor with a large coopetitive budget to the innovative coopetition agreement decreases the cooperation of the focal firm but increases the profit of the initial partnering firms. In contrast, the exit of a partnering firm with a large coopetitive budget from the agreement intensifies the cooperation among the remaining firms but reduces their profit.